2012
DOI: 10.1186/1471-2156-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Multiple trait multiple interval mapping of quantitative trait loci from inbred line crosses

Abstract: BackgroundAlthough many experiments have measurements on multiple traits, most studies performed the analysis of mapping of quantitative trait loci (QTL) for each trait separately using single trait analysis. Single trait analysis does not take advantage of possible genetic and environmental correlations between traits. In this paper, we propose a novel statistical method for multiple trait multiple interval mapping (MTMIM) of QTL for inbred line crosses. We also develop a novel score-based method for estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
1
27
0
7
Order By: Relevance
“…Usefulness of multi-loci approaches compared to single locus approaches were largely described in QTL mapping era678910111213141516. In GWASs, multi-loci association studies also have better performance as compared to the single-locus association studies161718.…”
mentioning
confidence: 99%
“…Usefulness of multi-loci approaches compared to single locus approaches were largely described in QTL mapping era678910111213141516. In GWASs, multi-loci association studies also have better performance as compared to the single-locus association studies161718.…”
mentioning
confidence: 99%
“…For all epistasis tests, we used a walk speed of 1 cM, a window size of 10, and a significance threshold of 0.10. The larger significance threshold ( vs. the traditional 0.05) was used since it has been shown that this increased value is more likely to capture significant effects but does not compromise the number of false positives [33].…”
Section: Methodsmentioning
confidence: 99%
“…Metodologias de mapeamento de QTLs mais modernas empregam a abordagem multivariada e se beneficiam da utilização da matriz de covariâncias fenotípicas para melhorar as estimativas de localização e efeitos de QTLs (JIANG;ZENG, 1995;HALEY, 2000;ZENG, 2010;ZENG, 2012). No entanto, em sistemas biológicos, os caracteres fenotípicos podem apresentar relacionamentos de causalidade entre si e os modelos multivariados baseados apenas em covariâncias não são capazes de levar tais relacionamentos em consideração (ROSA et al, 2011).…”
Section: Introductionunclassified